Callus cell and explants regeneration, glucose, mineral, antioxidant and flavonoid content development using broccoli root tip and leaf cutting in vitro: In vitro broccoli root tip and leaf cutting culture - Hossain, ABM Sharif; Alrudayni, Hassan A.; Haouala, Faouzi; Aleissa, Mohammed Saad; Kahrizi, Danial; Ahmed, Abu Saleh (Cellular and Molecular Biology, 2023)
The study was conducted to evaluate the root, shoot and leaf callus cell regeneration and its biochemical properties like antioxidant, carbohydrate, pigment and mineral content from broccoli root, shoot and leaf cutting in vitro. An in vitro factorial experiment was carried out based on a Completely Randomized Design (CRD) with 5 replicates in tissue culture applying different IBA (0.25, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0 and 3.5 mg/l) and BAP (1 mg/l) concentrations using broccoli root tip and leaf cutting. The results showed that a higher callus weight was found in the cultured leaf cutting than in root tip cutting in the concentration of 1.0, 1.5 & 2.0 mg/l IBA + 1.0 mg/l BAP combination. The highest callus weight was found in the cultured leaf cutting than root tips cutting at the concentration of 1.5mg/l IBA+1.0 mg/l BAP. Furthermore, the highest inverted sugar and glucose, chlorophyll and nutrient content (K+, NO3- & Ca++), total phenol, flavonoid and total antioxidant were found in the concentration of 1.5mg/l IBA+1.0 mg/l BAP combination in both broccoli leaf and root cutting. The results seemed that it was best to use the combination of the IBA and BAP in the concentration of 1.0-2.0 mg/l and 1mg/l to regenerate root, leaf and callus cell proliferation of broccoli from the root tip and leaf cutting.